The heart of Torah. Volume 2, Essays on the weekly Torah portion : Leviticus, Numbers and Deuteronomy - Held, Shai, 1971- (Philadelphia : Jewish Publication Society ; Lincoln : University of Nebraska Press, 2017)
In The Heart of Torah, Rabbi Shai Held s Torah essays two for each weekly portion open new horizons in Jewish biblical commentary. Held probes the portions in bold, original, and provocative ways. He mines Talmud and midrashim, great writers of world literature, and astute commentators of other religious backgrounds to ponder fundamental questions about God, human nature, and what it means to be a religious person in the modern world. Along the way, he illuminates the centrality of empathy in Jewish ethics, the predominance of divine love in Jewish theology, the primacy of gratitude and generosity, and God s summoning of each of us with all our limitations into the dignity of a covenantal relationship.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed August 17, 2017).
Master record variable field(s) change: 072
Keywords: Bible. -- Commentaries; RELIGION / Biblical Studies / Old Testament; RELIGION / Judaism / Theology; Electronic books